Performance outcomes in professional hockey players following arthroscopic treatment of FAI and microfracture of the hip - McDonald, John E.; Herzog, Mackenzie M.; Philippon, Marc J. (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2014)
Purpose Previous studies report professional athletes return to play following arthroscopic microfracture of the hip for chondral defects. Our hypothesis is that professional hockey players undergoing arthroscopic microfracture for chondral defects of the hip achieve the same performance they had pre-injury and compared to matched controls. Methods Seventeen professional hockey players underwent arthroscopic microfracture for an Outerbridge grade IV chondral lesion. Concomitant procedures for labral pathology or FAI were included. Performance data for the full season preceding and following index procedure were analysed, in addition to two matched control players per subject. Data were collected at two points, 2 years apart. Results Eighty-two per cent (14/17) of players who underwent arthroscopic microfracture returned to play. The year prior to injury for the 14 players who returned was compared to the average of their individual controls. There was no statistical difference between the groups for age, number of seasons in the league, games played, time on ice, points, save percentage, and shots against goal. Post-operatively, there was no statistical difference between the treatment and control groups regarding performance measures. There was a trend towards a decrease in games played and points post-operatively compared with controls. The treatment group decreased 11 games played, while the controls decreased five games. The treatment group also decreased 14 points, while the controls decreased three points for the season. Conclusions Professional hockey players with a discrete, full-thickness chondral defect of the hip are able to return to elite performance level following an arthroscopic microfracture procedure when compared to pre-injury outcomes and controls. Level of evidence III.